History of the Development of the Safavid Empire in Persia - Arieski Elfandi (Konsultan Jurnal Ilmiah Indonesia, 2025)
This research discusses the Safawi Kingdom which was established in the 16th century AD is one of the great empires in the Islamic world, centered in Persia (Iran) by adopting Shia Itsna Ashariah as a state ideology. The establishment of this kingdom was influenced by the Safawiyah order movement led by Safi al-Din in the 16th century AD. The development and progress of the Safawi Kingdom reached its peak during the reign of Shah Abbas I, who ruled from 1587 to 1629 AD. This research uses the library approach method (Library Research). Library research is a series of activities related to library data collection methods, reading and recording, and processing research materials by examining reading sources that have to do with the studies discussed in this study. During the reign of Abbas I, the kingdom experienced significant progress in the political, economic, religious and cultural fields, characterized by military success, political stability, and the development of arts and sciences. However, after its heyday, the kingdom began to decline due to various internal and external factors. These included internal conflicts, tensions with the Ottoman Empire, moral decadence on the part of some rulers, and divisions within the royal family. In the 18th century, the Safavid Empire finally collapsed and was replaced by the Qajar dynasty. The fall of the empire was part of a major change in Persian history that led to European influence and the establishment of colonial regimes. This article examines the historical journey of the Safavid Empire, from its emergence, to its peak, to the causes of its decline and fall.